Prediction of bending in SMC using a single parameter damage model that accounts for through thickness microstructural properties. (15th August 2020) - Sabiston, Trevor; Pinter, Pascal; Lee-Sullivan, Pearl; Inal, Kaan
Abstract: A micromechanics model that utilizes microstructural characteristics for predicting the bending stress-strain response of a SMC composite is presented. The model integrates matrix, interphase and fibre damage models to form a framework that is able to accurately represent the damage response of the SMC using a single parameter damage model that is equivalent to the von mises interfacial stress. This is a valuable capability given the inherent random nature of SMC properties. Before being subjected to three-point bending tests, three SMC samples from different areas of a molded plate were characterized using X-ray computed tomography. The through thickness properties such as fibre orientation and volume fraction were characterized for multiple layers and then used as input data for a finite element model to predict the stress-strain behaviour. It was found that prediction accuracy increased with more layer properties. The model was able to represent the stress strain results within 2% of the experimentally measured response using 12 microstructural layers for a 2.8 mm thick specimen.